Pelatihan Hidroponik Sistem Wick Bagi Ibu Rumah Tangga di Desa Semangat Karya Kabupaten Barito Kuala - Fuzi Maulana Ash'ari; Gusti Khairun Ni'mah; Yarna Hasiani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
One way to use house yard land to achieve household food security is to use the hydroponic method. Farming with the hydroponic method in utilizing narrow land in urban areas or in housing is not something new, but in the Semangat Karya Village, Barito Kuala Regency, it is still many do not know clearly how to grow a garden with the wick hydroponic method. The selection of the wick hydroponic system is because according to the Kementan (2018) this system is the simplest hydroponic model using a wick that connects plant pots with nutrient solution media. Therefore this service activity aims to provide knowledge and training to support skills in farming using the wick hydroponic method. This community service activity begins with filling out the pretest questionnaire followed by a presentation of the delivery of the material, then a demonstration of the direct method or practice and ends with the provision of a posttest questionnaire. The results showed that the wick system hydroponic training was able to increase the knowledge, understanding and skills of partners in plant cultivation using the wick system hydroponic method.